Distorsión armónica en la red eléctrica de Trujillo en función de la demanda de servicio y característica de carga - Méndez Gil, Vilma Julia (2008)
The electrical power is a basic service for the communities’ development. In this research work the voltage harmonic distortion of the electrical network of Trujillo city – Peru has been assessed. The measurements of the total voltage harmonic distortion factor, THDV, were carried out with the TOPAS 1000 device, according to the rules stipulated in the Peruvian electrical services regulation, D. S. Nº 020-2001, which establishes a control period of seven days, in recording intervals of 10 minutes. The data collection was made in the low voltage side of the transformation stations known as common connection points (PAC). The measurements were made in the randomly chosen 117 and 152 PACs during the 12 months of the years 2004 and 2005, respectively. It was found that the first four harmonics dominants of the Trujillo electrical network are the fifth, seventh, third and second ones. Taking into account the service demand, the harmonic distortion, THDV, reached its highest values of distortion in the afternoons and, even at the lowest service demand conditions, a distorted signal not lower than 0.61% of THDV was measured. By considering the load, in the year 2004 the harmonic distortion, THDV95, suffered the major variation in the current costumers (low power commercial – residential loads) while in the year 2005 the highest THDV95 variation occurred in the major costumers (high power commercial – industrial loads). Likewise, the THDV95, as an average, showed a tendency to increase along the 24 months. Furthermore, we have determined the total harmonic distortion of current, THDI, and the current harmonic spectrum which is injected to the network by loads such as personal computers and color television.